L'aide du numérique aux activités d'auto-évaluation - Stéphanie Mailles-Viard Metz
Self-assessment is a complex activity that is difficult to process, either for teacher or learner. Our goal is to reflect on the contribution of digital technology in this activity. At first, we try to define the concept regarding studies in educational sciences and psychology. The idea of measurement or analysis of his own work echoes with traces that the digital can record. Thus, in the second part, we develop the concepts of traces and appropriation, which are essential to understand the importance of the personalization of results. The last part of this text is devoted to a list of tools with implemented activities. We describe synchronous (chat) and asynchronous (forum) communication tools, sharing tools (blogs and e-portfolio), individual (mind maps) and collective (shared whiteboard) production tools and learning management tools (LMS and personal learning environment). We focus on the functionalities of these tools that make possible the self-analysis itself but also the sharing of information with other, an important dimension to judge the effectiveness of actions. The tools are illustrated by examples of teaching situations observed mainly in IUT (French Institute of Technology). In conclusion, we propose the implementation of a questioning from the teacher for the choice of the tool to meet its expectations, in particular, to allow the measurement of self-evaluation criteria whose definition depends on delimiting expectations produced beforehand.